Neural and fuzzy logic control of drives and power systems - Cirstea, M. N. (Marcian N.) (Oxford [England] ; Boston, MA : Newnes, 2002)
The authors guide readers quickly and concisely through the complex topics of neural networks, fuzzy logic, mathematical modelling of electrical machines, power systems control and VHDL design. Unlike the academic monographs that have previously been published on each of these subjects, this book combines them and is based round case studies of systems analysis, control strategies, design, simulation and implementation. The result is a guide to applied control systems design that will appeal equally to students and professional design engineers. The book can also be used as a unique VHDL design aid, based on real-world power engineering applications. *Introduces cutting-edge control systems to a wide readership of engineers and students *The first book on neuro-fuzzy control systems to take a practical, applications-based approach, backed up with worked examples and case studies *Learn to use VHDL in real-world applications.
Control systems -- Modern control systems design using CAD techniques -- Electric motors and power systems -- Elements of neural control -- Neural FPGA implementation -- Fuzzy logic fundamentals -- VHDL fundamentals -- Case studies: Neural current and speed control of induction motors; Fuzzy logic control of a synchronous generator set -- Appendices.
Includes bibliographical references (p. [294]-304) and index.
Keywords: Electronic controllers -- Mathematical models; Control theory; Fuzzy systems; Neural networks (Computer science).; Fuzzy logic; VHDL (Computer hardware description language).; Electric driving, Variable speed -- Automatic control; Electric machinery -- Alternating current -- Automatic control; Electric motors -- Electronic control; Electronic books